2022
DOI: 10.3389/fpsyt.2021.810274
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Mental Well-Being During the COVID-19 Pandemic: Serial Mediation by Persistent Thinking and Anxiety About Coronavirus

Abstract: Reports to date indicate that the COVID-19 pandemic outbreak has negatively impacted mental health in the general population. On the other hand, positive associations of mental resilience and well-being have been widely demonstrated. The objective of this study was to assess the links between resilience (Brief Resilience Scale), persistent thinking about COVID-19 (Obsession with COVID-19 Scale), coronavirus anxiety (Coronavirus Anxiety Scale), and well-being (World Health Organization's 5-item Well-being Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
(62 reference statements)
1
26
0
2
Order By: Relevance
“…During pandemics, there is an opportunity to improve HCWs’ ability to cope with and manage stress by building their resilience as a complementary approach to the necessary systemic efforts required. Recent studies also demonstrated that increased resilience has been linked to less persistent thinking about COVID-19 and increased wellbeing ( Skalski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During pandemics, there is an opportunity to improve HCWs’ ability to cope with and manage stress by building their resilience as a complementary approach to the necessary systemic efforts required. Recent studies also demonstrated that increased resilience has been linked to less persistent thinking about COVID-19 and increased wellbeing ( Skalski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other interventions that have been effective in improving the coping skills of college students include cognitive-behavioral therapy, mindfulness mediation, and online coping tools (Kang et al, 2009 ; Regehr et al, 2013 ; Molla Jafar et al, 2015 ; Phang et al, 2015 ; Houston et al, 2017 ; Yusufov et al, 2019 ; Freire et al, 2020 ). Given that resilience has also been shown to help mediate stress and improve mental well-being during the COVID-19 pandemic, interventions focusing on enhancing resilience should be considered (Surzykiewicz et al, 2021 ; Skalski et al, 2022 ). Telemental health resources across colleges can also be implemented to reduce stigma and improve at-risk students' access to care (Toscos et al, 2018 ; Hadler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research with medical, nursing, and pharmacy students demonstrates correlations of resilience with positive well-being and academic success [ 66 ]. Likewise, in a study of the general public in Poland that used the BRS, enhancing resilience was found to reduce negative mental effects during the pandemic [ 67 ]. As such, the development of resilience in our students will better prepare them for academic achievement and ensure a smooth transition into their professional roles, especially amidst various educational, financial, and health challenges.…”
Section: Discussionmentioning
confidence: 99%